Enzyme electrode for glucose oxidation using low‐solubility 4‐aminodiphenylamine derivatives as electron mediator. Issue 4 (26th June 2021) - Masakari, Yosuke; Totsuka, Naoya; Shinohara, Yasutomo; Yoshida, Shotaro; Abe, Hiroya; Ito, Kotaro; Nishizawa, Matsuhiko
Abstract: A novel enzyme electrode system for glucose oxidation was constructed by co‐immobilization of glucose dehydrogenase (GDH) and N, N '‐diphenyl‐ p ‐phenylenediamine (DPPD) on carbon electrodes. This enzyme electrode system was applied to porous carbon fabric to produce a glucose oxidation current of 7 mA/cm 2, while the electrode catalytic activity was maintained at approximately 100% for more than 4 h, indicating that DPPD molecules were stably retained on the electrodes during the continuous redox cycling. Further, a stable mediation was also observed for other 4‐aminodiphenylamine derivatives similar to DPPD. The difference was found in the adsorptivity between the reduced and oxidized forms of DPPD on the carbon electrode, suggesting that a portion of oxidized DPPD can access the active center of GDH without desorbing to solution. This electrode system with 4‐aminodiphenylamine derivatives can be used in sensors for glucose monitoring and to anodes of separator‐free glucose fuel cells. Abstract : Enzyme electrode can be prepared using 4‐aminodiphenylamine derivatives ( N, N '‐diphenyl‐ p ‐phenylenediamine; DPPD) as mediator molecules without covalent immobilization on the electrode. The proposed system was applied to carbon fabric to produce a glucose oxidation current of 7 mA/cm 2, while the electrode catalytic activity was maintained at approximately 100% for over 4 h.